Process Evaluation of Residential Substance Abuse Treatment Programs in Maine, 1999-2000 - Hawke, Josephine M. ([Verlag nicht ermittelbar], 2003)
The State of Maine Department of Corrections (MDOC) and the Office of Substance Abuse (OSA) at the Maine Department of Mental Health, Mental Retardation and Substance Abuse Services opened the Key Maine Therapeutic Community (TC) in March 1999, and its Transitional Treatment Program (TTP) for adult male inmates in January 2000. Spectrum Behavioral Services, Inc. (SBC) was subcontracted to implement the program, which was located at the Maine Correctional Facility in South Windham and the Pre-Release Center in Hallowell. The United States Department of Justice Residential Substance Abuse Treatment (RSAT) funded the initiative. This study was undertaken as a process evaluation of the program. To accomplish the aims of the process evaluation, research staff examined both program and client-level data that were collected throughout the first 15 months of the Key Maine TC's operation, a period that included the initial start-up period for the TTP. Part 1, Baseline Data, contains information on inmates, including age, ethnic group, education level, timing of all diplomas or degrees they had received, reasons for stopping school, marital and/or relationship status and history, and number and ages of children. The file also includes information on the last six months before being incarcerated, such as attendance at religious services, kind of housing and time spent there, as well as whom they lived with and the behavior of the inmate and their living companions in terms of alcohol and drug use. Also, there is information about how respondents supported themselves financially, including employment status and job information, such as number of days worked, number of jobs, part-time or full-time status, income, supplemental income, drug and alcohol use effects on employment, and whether they had dependants to support. In addition to information on the six months before incarceration, the file provides information on the inmate's substance abuse behaviors over his lifetime, including specific drugs used, the frequency used, and the age at which use of particular substances began. Information on substance abuse behaviors, such as specific substances used and frequency used in the last 30 days, is also recorded. Other variables in Part 1 focus on whether inmates' substance abuse had caused problems in major areas of their lives, such as family, employment, school, physical and mental health, relationships, and other substance abuse treatment received, including the type of treatment, duration of treatment, main substance abused, and reasons for entering treatment. Self-report data are available on each inmate's lifetime history of illegal activities, including, but not limited to, arrest history. This includes the offense(s) for which the inmate was currently serving time, as well as past offenses, jail time served, number of times incarcerated, illegal activities in which the inmate engaged during the last six months before incarceration, and time spent in probation during the last six months before incarceration. Information on visitors received during time in jail and contact (phone calls and letters) with others while in jail are included, as well as personal history information concerning the inmate's relationship with family and the activities they engaged in together. There is information on the friends the inmate had during the six months before incarceration, such as their education level, employment status, and relationship with family. Additional variables include whether the inmate reported having a history of child abuse, with details such as age at time of abuse, relationship with the abuser, frequency of abuse, perceived association of child abuse history to the inmate's substance abuse, the inmate's history as both victim of and perpetrator of violent crimes and weapon use, the inmate's sexual activity during the six months before incarceration, and his opinions about the chances of contracting HIV/AIDS. Other items pertain to behaviors that increase the risk of contracting HIV/AIDS and the inmates' feelings about HIV/AIDS, such as whether they worried about contracting the virus, whether they would want to know if they had the virus, whether they knew how to protect themselves, whether they had altered their behavior to reduce their chances of infection, and their perceptions regarding the likelihood of contracting HIV/AIDS. Part 1 data also provide information on inmates' physical and mental health, along with medications taken and diagnosed mental disorders. Interviewers' ratings concerning the inmates' behavior during the interview and whether the interviewer believed the inmates would complete the program are assessed across 16 areas. Part 2, Retention Data, indicates how long inmates spent in the program and the reason for their discharge. Part 3, Score Data, provides the inmates' psychological and motivational scores for the short self-esteem index, the short depression index, motivation and readiness and treatment engagement, and when they were tested. Also included are scores for counselor rapport and counselor competence. Part 4, Services Data, records the number of times an inmate had used particular services, such as clinical groups, clinical supervision, educational sessions, encounter groups, group counseling sessions, individual counseling sessions, seminars, and 12-step sessions.